(untitled) (Microbes and Health, 2013)
Bottled water has become one of the most popular drinks in Bangladesh. Now a days it is easily available in the market. The objectives of this study were to assess the overall quality (qualitative and bacteriological) of bottled water samples in the city of Mymensingh, Bangladesh. For achieving the objectives, standard questionnaire, methods of heterotrophic plate count (HPC) and total coliform count (TCC) were applied. Qualitative assessment of bottled water indicated that a good number of people preferred bottled water to tap water. The criterion in order to qualify for a good bottled water was the taste (43.3%). The bottled water quality was satisfactory in 40% of the responders in this study on the basis of peoples satisfactions, perceptions and expenditures on bottled water quality. On the other hand, the percentage of dumping of bottled water after consumption refuse was 33.3%. Monthly expenditure on bottled water was less than 300 taka in 80% of the responders. The geometric mean of HPC of different brands of bottled water ranged from 2.9x103 cfu/100 ml to 6.2x103 cfu/100 ml. In addition, the geometric mean of TCC of different brands of bottled water ranged from 9 cfu /100 ml to 43 cfu /100 ml. The results indicate that most of the bottled water studied were out of their safety guidelines. Recommendations for better treatment systems for bottled drinking water to address the issue appears to be essential. DOI: http://dx.doi.org/10.3329/mh.v1i2.14096 Microbes and Health, 2012 1(2): 81-85